Analytical Shaping of a Rocket Nose as a Stage of Preliminary Aerodynamic Modification - Adrian Szklarski; Robert Głębocki (Aerospace)
The article discusses the problem of a preliminary analytical method for modifying the shape of a rocket’s nose. The purpose of this method is to determine the shape that minimizes aerodynamic drag, in the context of modifying a ballistic missile to incorporate guidance systems. The traditional design process relies on numerical methods such as CFD (Computational Fluid Dynamics) or machine learning techniques; however, the method presented here can serve as a first iteration to support the design. Advanced simulation tools are often expensive and difficult to access for smaller companies, while open-source software can sometimes be unreliable, difficult to use, and incompatible with professional solutions. This can pose a challenge for businesses planning to collaborate in the future with large corporations that rely on advanced engineering tools. The proposed solution, as previously mentioned, provides a starting point for the entire design process. The approach has been shown to be sufficient from the design work. The entire process was validated during test range trials, during which rockets were launched, and the flight measurement results accurately reflected the aerodynamic properties of the missiles. In the next stages of the project, numerical methods including CFD simulations are planned to verify the analytical results and enable further aerodynamic modification of the design.